2002
DOI: 10.1128/jb.184.23.6739-6745.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Viable but Nonculturable State and Starvation Are Different Stress Responses of Enterococcus faecalis , as Determined by Proteome Analysis

Abstract: The protein expression patterns of exponentially growing, starved, and viable but nonculturable (VBNC) Enterococcus faecalis cells were analyzed to establish whether differences exist between the VBNC state and other stress responses. The results indicate that the protein profile of VBNC cells differs from that of either starved or exponentially growing bacteria. This demonstrates that the VBNC state is a distinct physiological phase within the life cycle of E. faecalis, which is activated in response to multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
143
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(155 citation statements)
references
References 35 publications
5
143
0
1
Order By: Relevance
“…However, it is becoming clear that many pathogens can enter a viable but non-cultivable state (VBNC) when exposed to various chemical or environmental factors. E. faecalis was shown to enter the VBNC state in response to low nutrient concentration, osmotic or oxidative stress and low temperature [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is becoming clear that many pathogens can enter a viable but non-cultivable state (VBNC) when exposed to various chemical or environmental factors. E. faecalis was shown to enter the VBNC state in response to low nutrient concentration, osmotic or oxidative stress and low temperature [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence on the revival of growth in these dormant cells, a number of basic and logical questions have been raised as to whether this nonculturability is a dormancy state of cell adaptation to stress or a stage preceding cell death, partly owing to the unpersuasive revitalization potential. Studies also showed the molecular and functional dissimilarity of stressed (Chan et al 1998), VBNC cells (Heim et al 2002) from the NC state induced by "starvation", which was demonstrated using isolated NC cells (Desnues et al 2003), leading to the suggestion that NC cells might have been formed as a result of stochastic deterioration. Nonetheless, while co-crystallization of DNA with the stress induced proteins was proposed as a generic defense strategy to environmental stress in Escherichia coli (Wolf et al 1999), a resuscitation-promoting factor(s) (Rpf) was also identified in long-term stationary phase cultures of Micrococcus luteus (Mukamolova et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Several starvation-survival responses have been described, with starved bacterial populations maintaining their numbers over time in a non-growing but culturable state at different levels depending on the species (Morita, 1997). This starvation-induced state for survival proved to be distinctly different from that of active growth (Heim et al, 2002). Under prolonged oligotrophy, reduction in cell size and change to a round cell shape are also considered as bacterial strategies to survive in the environment (Novitsky & Morita, 1976;Rollins & Colwell, 1986;Ruiz et al, 2001), as well as the induction of a viable but non-culturable (VBNC) state (Oliver, 2005;Roszak & Colwell, 1987) that constitutes a distinct physiological state from that of the starvation response (Heim et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This starvation-induced state for survival proved to be distinctly different from that of active growth (Heim et al, 2002). Under prolonged oligotrophy, reduction in cell size and change to a round cell shape are also considered as bacterial strategies to survive in the environment (Novitsky & Morita, 1976;Rollins & Colwell, 1986;Ruiz et al, 2001), as well as the induction of a viable but non-culturable (VBNC) state (Oliver, 2005;Roszak & Colwell, 1987) that constitutes a distinct physiological state from that of the starvation response (Heim et al, 2002). R. solanacearum becomes VBNC by exposure to copper (Grey & Steck, 2001) and after incubation at low temperature in soil and water (Caruso et al, 2005;van Elsas et al, 2000van Elsas et al, , 2001van Overbeek et al, 2004).…”
Section: Introductionmentioning
confidence: 99%